PENERAPAN METODE DEMOSNTRASI TERHADAP PROSES PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS DI TK YA BUNAYYA KELAS ADI KABUPATEN SAMBAS - Novi Cahya Dewi (CV. Adiba Aisha Amira, 2023)
Discussion on how to teach using the demonstration method for children with Down syndrome in class A Kindergarten Ya Buyanayya, Sambas district. The method used is descriptive research method with a qualitative approach. The data source consisted of 1 teacher, 4 children with special needs (Down Syndrome) in class A. The results of the study described how children with Down syndrome learn to do individually according to the child's level of ability and development. The teacher's way of teaching children with Down syndrome is by giving direct assignments and inviting children to imitate the teacher's words. The tasks given include the activity of writing letters and numbers using the demonstration method, then for learning to memorize surahs and hadiths the teacher uses the murroja'ah method for children with special needs (Down Syndrome). This learning can be known by parents through good cooperation between teachers and parents.